PENGARUH PENGENDALIAN INTERNAL DAN GOOD CORPORATE GOVERNANCE TERHADAP PENCEGAHAN FRAUD - Nugroho, Dennyca Hendriyanto; Afifi, Zaenal (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2022)
This study aims to determine: (1) The effect of internal control on fraud prevention, (2) The influence of good corporate governance on fraud prevention, (3) The effect of internal control on good corporate governance. This research was conducted at the People’s Credit Bank (BPR) spread across Kudus Regency. This study used a data collection technique by distributing questionnaires at rural banks in Kudus Regency with the collection of 118 respondents. The obtained questionnaires were tested using validity and reability to test the feasibility of the obtained questionnaire data. The test equipment used in this study was to use the analysis requirements test including normality test, multicolonierity test, heteroskedasticity test. The method used in data analysis is a multiple regression analysis model. The results of this study show that: (1) internal control variables have a positive and significant effect on fraud prevention, (2) Good corporate governance variables have a positive and significant effect on fraud prevention, and (3) Internal control variables have a positive effect on good corporate governance